Faktor-Faktor yang Mempengaruhi Kinerja Keuangan Universitas Pattimura dengan Peran Satuan Pengawas Internal sebagai Variabel Moderasi - Galio Publius Manuputty; Jozef Richy Pattiruhu; Stenly Jacobus Ferdinandus (Jurnal Simki Economic, 2026)
This study aims to analyze the factors influencing the financial performance of Pattimura University, with the role of the Internal Audit Unit (SPI) as a moderating variable. The independent variables used include budget planning, budget execution, and budget control. This study employed a quantitative descriptive approach with primary data obtained through questionnaires distributed to 46 respondents, consisting of budget managers and SPI members. Data analysis used the Partial Least Squares (PLS) method. The results indicate that budget planning, implementation, and control have a positive influence on financial performance. Furthermore, the role of the SPI also has a direct influence on financial performance and moderates the relationship between budget variables and financial performance. These findings suggest that strengthening the internal audit function can improve the effectiveness of financial management in higher education institutions. This study emphasizes the importance of improving financial governance within universities based on the principles of accountability and transparency.